The Influence of Transformational Leadership Through Delegation on Work Efficiency in Senior High Schools in Merangin District - Mardalena Mardalena; Sarinah Sarinah (JURNAL INOVASI DAN MANAJEMEN PENDIDIKAN, 2025)
The purpose of this study is to examine how transformational leadership through delegation affects teachers' productivity at SMAN Merangin.  102 teachers from three senior high schools (SMAN) in Bangko, Merangin, Jambi, participated in the study's quantitative survey design.  Structural Equation Modeling (SEM) with SmartPLS 4 was used to analyze the data.  The measurement tools were modified from Yukl (2020) for delegation, Moeheriono (2020) for work efficiency, and Bass & Riggio (2019) for transformational leadership.  Composite Reliability (CR) > 0.70 and Average Variance Extracted (AVE) > 0.50 indicated strong construct reliability and convergent validity, as demonstrated by the validity and reliability tests. The findings show that delegation has a significant impact on work efficiency (β = 0.49, p < 0.01) and that transformational leadership has a significant impact on delegation (β = 0.58, p < 0.01).  Additionally, the relationship between transformational leadership and work efficiency is mediated by delegation, indicating that effective delegation techniques amplify the beneficial effects of transformational leadership on teacher performance. The study's conclusions imply that, to improve teacher autonomy, accountability, and productivity, school administrators should emphasize delegation as a crucial component of transformational leadership.  Enhancing principals' delegation skills should be the main goal of leadership development programs and training courses.  To encourage long-term effectiveness and teacher empowerment, education policymakers may incorporate delegation-based leadership models into school management frameworks.